The Effect of Reminiscence Exercise Therapy and Nursing Resource Management on the Psychological Well-being of Elderly in Nursing Homes: A Multi-Perspective Study - Mendrofa, Fery Agusman Motuho (Public Health of Indonesia, 2025)
Background: The aging population in Indonesia continues to grow rapidly, with projections reaching 19.8% by 2045 according to Indonesia's Central Bureau of Statistics (2022). Elderly individuals in nursing homes face complex physical and psychosocial challenges that require comprehensive interventions. Objectives: This study aimed to analyze the combined effect of Reminiscence Exercise Therapy (RE) and nursing resource management optimization on the psychological well-being of elderly residents in nursing homes. Method: This study employed a quasi-experimental design with a sequential explanatory mixed-methods approach. The quantitative component used a pre-post test design with three groups (n=72): RE intervention with nursing resource management optimization (combined intervention), RE intervention only, and control group. Data collection included Geriatric Depression Scale (GDS-15), Satisfaction With Life Scale (SWLS), and Timed Up and Go (TUG) test. The qualitative component involved in-depth interviews with nurses (n=12) and managers (n=6) to explore implementation processes. Results: Both intervention groups showed significant improvements in all three parameters compared to the control group (p<0.001). However, the combined intervention group demonstrated significantly greater improvements than the RE-only group in GDS-15 scores (mean difference -1.46, p=0.023), SWLS scores (mean difference 3.45, p=0.002), and TUG test (mean difference -1.44 seconds, p=0.034). Qualitative analysis identified four main themes: (1) synergy between reminiscence-based care and management practices, (2) empowerment of nursing staff in person-centered care approaches, (3) optimization of resource allocation for reminiscence activities, and (4) implementation barriers at system level. Conclusion: An integrated approach combining Reminiscence Exercise Therapy with nursing resource management optimization is significantly more effective in improving psychological well-being and functional mobility of elderly nursing home residents compared to RE Therapy alone or standard care. This study highlights the importance of considering organizational and management factors when implementing psychosocial interventions in nursing homes. Future research should explore the long-term sustainability of this integrated approach in various organizational contexts.